High energy density and efficiency in (Pb, La)(Zr, Sn, Ti)O3 antiferroelectric ceramics with high La3+ content and optimized Sn4+ content. Issue 18 (15th December 2019) - Yu, Yuxi; Zhang, Yangyang; Zou, Kailun; Chen, Guang; Zhang, Ying; Li, Hao; Lu, Yinmei; Zhang, Qingfeng; He, Yunbin
Abstract: In this work, to simultaneously obtain a high recoverable energy density ( W re ) and efficiency ( η ) in one kind of material, we investigate the effects of Sn 4+ content on the energy storage capacity of (Pb0.955 La0.03 )(Zr0.50 Sn x Ti0.50- x )O3 antiferroelectric (AFE) ceramics with a high La 3+ content. La 3+ can cause polarization-electric field ( P - E ) loops to narrow down, therefore, resulting in a good energy storage performance. On account of the replacement of Sn 4+ with larger ion radius for Ti 4+, the tolerance factor decreases, and therefore, the AFE phase stability improves. This modification results in an enhancement of the ferroelectric-antiferroelectric phase switching electric field ( E A ), which favours an increase in W re . However, at the same time, with the increase of Sn 4+ content, the maximum polarization decreases, which can lead to a deterioration in W re . As a result, the optimal energy storage performance is achieved in the (Pb0.955 La0.03 )(Zr0.50 Sn0.42 Ti0.08 )O3 AFE ceramic, which possesses a high W re (3.99 J/cm 3 ) and η (79.2%). Additionally, the W re and η exhibit a good temperature stability from 25 to 125 °C. These results indicate that this kind of ceramic can be used to prepare dielectric capacitors for working in different environments.